Rate-dependent plasticity models derived from potential functions - Houlsby, G; Puzrin, A (2002)
The constitutive behavior of the rate dependent plasticity models derived from potential functions was discussed. The potential functions were energy function and the flow or force potential. These potentials were related through a series of Lengendre-Fenchel transformations. After the specification of the potentials, an entirely standardized procedure was adopted to derive the response. There is a transparent link between the terms that appear in the potentials, and the results in terms of constitutive response.